SENSIBLE HEAT TRANSFER ON ATMOSPHERIC-OCEANIC BOUNDARY IN THE OUTER AMBON BAY OF INDONESIA - Salamena, Gerry Giliant (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2013)
Analysis of air-sea temperatures and sensible heat flux was conducted to investigate heat transfer process on the atmospheric-oceanic boundary for the outer Ambon Bay. The analysis used SST data derived from both satellite product and in situ measurement using linear regression method, as well as meteorological data such as air temperature and wind speed during daytime. The goals of the current work were to evaluate the relationship between SST and air temperature in the outer Ambon Bay, and to investigate the variation of sensible heat flux in association with seasonal variability of the bay. The major findings were: 1) SST was predominantly lower than airtemperature, resulting in the dominance of negative feedback process on the atmospheric-oceanic boundary layer of the bay; 2) the seasonal SST variability was influenced by land heating and upwelling in the Banda Sea; 3) land heating resulted in large gradient of air-sea temperatures, whereas cooler upwelled waters exerted an opposite effect.